Active optical clock lasing on the Cs 7S1/2-6P3/2 transition under a weak magnetic field - Shi, Tiantian; Miao, Jianxiang; Zhang, Jia; Chen, Jingbiao (Frontiers in Physics, 2022)
In the bad-cavity limit, the collective atomic dipole is highly coherent, resulting in the phase information of active-optical-clock (AOC) laser primarily stored in the atomic gain medium. Therefore, compared with the good-cavity laser, the sensitivity of AOC laser to external thermal noise is greatly reduced, as characterized by the suppressed cavity-pulling effect. In addition, the quantum-limited linewidth of AOC laser can be further narrowed owing to its inhibition on the cavity-length noise. In this work, the AOC lasing on the cesium 7S_1/2-6P_3/2 clock transition with natural linewidth of 1.81 MHz under weak magnetic field is achieved. We calculate the Zeeman spectra of upper and lower states of clock transition, and measure the beat-note spectrum between different Zeeman sublevel transitions of 7S_1/2-6P_3/2. Moreover, the cavity-pulling, temperature, power and linewidth characteristics of the AOC laser are demonstrated under weak magnetic field. Such an emerging laser can be applied as the narrow-linewidth local oscillator, as well as the active optical frequency standard, which is promising on the field of precision measurement.